Atomic Layer Deposition of Metal Oxides in Perovskite Solar Cells: Present and Future. Issue 12 (13th September 2020) - Xing, Zhi; Xiao, Junjun; Hu, Ting; Meng, Xiangchuan; Li, Dengxue; Hu, Xiaotian; Chen, Yiwang
Abstract: In recent years, the development of perovskite solar cells (PSCs) is advancing along the way, and the efficiency is comparable to traditional silicon‐based solar cells. However, as crucial factors in the road to commercialization, stability and upscaling manufacture have not been fully investigated yet. To solve these problems, the exploration of charge transport layer (CTL) is clearly imminent, which is critical to the stability of PSCs. Among them, inorganic metal oxides have better stability than organic CTL. Particularly, the atomic layer deposition (ALD) process can fabricate dense and scalable metal oxides based on the self‐limiting surface reaction. This perspective focuses on the recent progress of ALD‐grown metal oxides in PSCs: both of electron and hole transport layer; connection layer in tandem architectures; application in semi‐transparent perovskite solar cells (ST‐PSCs); prospective of commercialization feasibility of the ALD‐grown metal oxides in ST‐PSCs. Abstract : As a key factor affecting the performance and stability of perovskite solar cells, the application of the interface layer is crucial. This review summarizes that ultra‐dense and stable metal oxide layers can be prepared by atomic layer deposition for application in perovskite solar cells, and their commercial feasibility is prospected.